(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
The article aims to analyze the allegory project of the G.R.E.S. open-wings. Caprichosos de Pilares, submitted to prior censorship for approval of the 1984 Carnival. Using photographs of the opener on the day of the parade, published in Revista Manchete and Jornal do Brasil, analyze how the allegory was constructed. With this set of images, it is possible to observe the differences between the project and the conception of the allegory for the 1984 parade.